Corporate social reporting revisited - Ariane Berthoin Antal; Meinolf Dierkes; Keith MacMillan; Lutz Marz (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
The intensity and scope of attention to the (negative) impacts of business activities on the social and natural environment have waxed and waned over the past forty years. A revival of interest on a wide scale is visible and audible again today. Numerous organizations, including the United Nations, the European Commission, national governments, and public interest groups, are calling for business to publish reports documenting their impacts on society and the environment. What can be learned from the early years of work in the area of corporate social responsibility and responsiveness, and how must the methods be altered in light of the changes that have occurred in the way the topic is defined today and in light of the new media available, especially the internet? This article tackles these two questions first by recalling which of the original concepts were found particularly useful, outlining their key strengths and weaknesses, and then by exploring the factors that currently characterize the field. – – Die Diskussion über die Auswirkungen von Unternehmensaktivitäten auf die soziale und natürliche Umwelt hat in den letzten vierzig Jahren große konjunkturelle Schwankungen erfahren. War zu bestimmten Zeiten die Intensität sehr hoch, mit der soziale Forderungen an die Unternehmen gestellt wurden, konnte man zu anderen Zeitpunkten, besonders unter der Dominanz des neoliberalen Wirtschaftsparadigmas, beobachten, wie die Verantwortung des Unternehmens gegenüber der Bezugsgruppe Anteilseigner unter dem Schlagwort shareholder value im Vordergrund der Diskussion stand. Heute ist in großem Umfang und in vielen Ländern ein Neuaufleben des Interesses an einer breit definierten gesellschaftlichen Verantwortung der Unternehmen festzustellen.
Keywords: 330; Sozialbilanz; Umweltbilanz; Öffentlichkeitsarbeit; Welt